Asymptotic properties of GEE estimator for clustered ordinal data with high-dimensional covariates. Issue 4 (16th February 2023) - Chen, Xianbin; Yin, Juliang
Abstract: Clustered ordinal data with high-dimensional covariates have become increasingly common in social and biomedical sciences. In this paper, we consider some asymptotic properties of generalized estimating equations (GEE) estimator in the case that the dimension of covariates goes to infinity as the sample size tends to infinity for such data. Under some regularity conditions, the existence, consistency and asymptotic normality of GEE estimator are proved. Besides, the effectiveness of asymptotic approximation is illustrated via numerical simulations. Our main result generalizes that of Wang [The Annals of Statistics, 39(1): 389–417, 2011] to the case of multinomial response variable.